The PengaruhTerapi Doa Kristiani Terhadap Tingkat Kecemasan Pasien - Niman, Susanti; Silvana, Angelina Resti; Hardjanti, CB, Sr. Therese Maura (Jurnal Keperawatan Florence Nightingale, 2024)
Patients undergoing treatment in inpatient settings often experience concerns related to pain, anxiety, the potential for death, and risks to physical safety. The anxiety experienced by the patient must be intervened so as not to affect psychological well-being. Anxiety interventions can be carried out independently by nurses in the form of spiritual therapy: Christian prayer. Objective the study to analyze the effect of Christian prayer therapy on anxiety levels in inpatients. This is Quasi-experimental study on 23 hospitalized respondents, Christian and Catholic and experiencing anxiety. Respondents were selected using purposive sampling. The Hamilton Anxiety Rating Scale (HARS) questionnaire was used to measure anxiety and Christian prayer therapy intervention with a prayer module given for 10-15 minutes in 4 meetings. 23 respondents were given Christian prayer therapy with 16  female respondents(70%.) The mean anxiety before the intervention was 21.17, and after the prayer intervention, it was 5.39. The results of the Wilcoxon Rank Sum test showed an influence of Christian prayer therapy on anxiety levels (p-value 0.0005). There is a statistically significant difference between anxiety before and after Christian prayer therapy. Christian prayer therapy interventions can help patients manage anxiety during hospitalization. The prayer module can be used by nurses in assisting Christian and Catholic inpatients who experience anxiety